Reducing vessel noise increases foraging in endangered killer whales. (December 2021) - Williams, Rob; Ashe, Erin; Yruretagoyena, Laurel; Mastick, Natalie; Siple, Margaret; Wood, Jason; Joy, Ruth; Langrock, Roland; Mews, Sina; Finne, Emily
Abstract: Disturbance from underwater noise is one of the primary threats to the critically endangered southern resident killer whales (SRKWs). Previous studies have demonstrated that SRKWs spend less time feeding when vessels are present. In 2018, we measured the effects of a voluntary vessel slowdown action in SRKW critical habitat to assess whether ship speed (and related source level) affects foraging behaviour. Observations of SRKWs and ships were collected from land-based sites on San Juan Island, WA, USA, overlooking the Haro Strait slow-down area. Exploratory analyses found little support for a linear relationship between ship speed and SRKW behaviour, but strong support between received noise level from ships and the probability of SRKWs engaging in foraging activity. Reducing ship speed, and therefore ship noise amplitude will help decrease the probability of ship noise disrupting SRKW foraging activity and may help to increase the proportion of accessible salmon. Highlights: Noise and disturbance threaten recovery of endangered southern resident killer whales (SRKWs) A voluntary ship slow down aimed to minimize noise in SRKW critical habitat. Slowing ships reduces noise level at the source, but increases duration of exposure. Reduction in ship speed and noise increased SRKW foraging behaviour. To set precautionary noise targets, we need new research on foraging time needed for whales to meet energetic demands.